Towards an evidence based urban design and planning practice; developing a digital tool prototype for designing based on the the theory of natural movement - Nyberg, Samuel (My University, 2025)
In times of increasing urbanization, population growth, and climate change, densification has been identified as a key strategy for sustainable urban planning. However, denser cities come with challenges on their own. By employing evidence-based design (EBD) approaches, urban planners can better understand how the built environment affects, and is affected by, peoples experience and use of it. Bill Hillier proposed one such approach with Space syntax and the Theory of Natural Movement, which aids urban planners in planning urban environments which facilitates human activity. This theory is the core concept for this thesis due to its ability to show the relationship between the street network, the distribution of density, and the flow of pedestrians, in cities and urban settings, which makes it a suitable framework for combining different quantitative morphological methodologies and investigating their relationship. This thesis aims to contribute to the implementation of EBD approaches in urban planning and design by proposing a way in which practitioners can use the Theory of Natural Movement to guide both the planning of streets and the distribution of function in an integrated process at early design stages and prototyping a digital tool which makes use of these conclusions. Three research areas are investigated: first, a literature review of the core concepts of the Space syntax and Spacematrix methodologies, which act as the primary theoretical methodologies for the thesis; second, an overview of existing digital tools to understand how they support urban planning practice; and third, a case study into Swedish planning documents and practice based on Backaplan, Gothenburg, together with a workshop with the Gothenburg urban planning office. Based on this research, a prototype for a digital tool is developed. Based on a simple urban model consisting of simply surfaces and networks, the tool promotes a design process based on the Theory of Natural Movement by using the network as the primary design tool and facilitating network- and surface-based analysis for a comprehensive outcome assessment. The basic functionality is described together with an example design process to better understand the steps involved both for user and software
Keywords: Theory of Natural Movement, Space Syntax, Spacematrix, Evidence-Based Design, Digital Tool